TEKNIK COMPOSITING DENGAN GAYA LOTTE REINIGER DALAM FILM ANIMASI PENDEK “MONSTER OF THE DARK VALLEY” - Prastiwi, Indah (Jurnal Ilmu Komunikasi AKRAB, 2017)
ABSTRACTIn the making of an animation work there are various forms of style, one of them is a silhouette animation. Silhouette animation become popular because of an animator and a German director named Lotte Reiniger. In the creation of her work she uses the technique of compositing manually by her hands and compose the layer to be beautiful by stacking several layers. The Monster of The Dark Valley works using compositing techniques that adapt from the technique of Lotte Reiniger?s. With a story that is a fictional, Monster of The Dark Valley style fits the Lotte Reiniger?s style animation that mostly story of fairy tales. The Monster of The Dark Valley is a short 4-minute animated film that tells of a child with a different physique then the most, so he avoided by the peoples of his village. The creation of this work is also supported by the study of existing works that inspired the author in creating this work, and in it?s implementation the study has been used. Compositor plays a role in combining a good layer with the composition object, color, and size of elements that previously created in the animation production stage. Lotte Reiniger?s style compositing technique has been implemented in making Monster Of The Dark Valley works by stacking multiple layers and creating a foreground layers. Lotte Reiniger?s compositing techniquestyle strongly supports the creation of Monster of The Dark Valley so that the work becomes beautiful, interesting and has a balanced composition.Kata Kunci: Animasi Silhouette, Lotte Reiniger, Compositing